Functional disintegration in paranoid schizophrenia using resting-state fMRI - Zhou, Yuan; Liang, Meng; Tian, Lixia; Wang, Kun; Hao, Yihui; Liu, Haihong; Liu, Zhening; Jiang, Tianzi (Schizophrenia research, 2007)
Functional disintegration has been observed in schizophrenia during task performance. We sought to investigate functional disintegration during rest because an intrinsic functional brain organization, including both “task-negative” (i.e., “default mode”) and “task-positive” networks, has been suggested to play an important role in integrating ongoing information processing. Additionally, the brain regions that are involved in the intrinsic organization are believed to be abnormal in schizophrenia. Patients with paranoid schizophrenia ( N = 18) and healthy volunteers ( N = 18) underwent a resting-state fMRI scan. Functional connectivity analysis was used to identify the connectivity between each pair of brain regions within this intrinsic organization, and differences were examined in patients versus healthy volunteers. Compared to healthy volunteers, patients showed significant differences in connectivity within networks and between networks, most notably in the connectivities associated with the bilateral dorsal medial prefrontal cortex, the lateral parietal region, the inferior temporal gyrus of the “task-negative” network and with the right dorsolateral prefrontal cortex and the right dorsal premotor cortex of the “task-positive” network. These results suggested that the interregional functional connectivities in the intrinsic organization are altered in patients with paranoid schizophrenia. These abnormalities could be the source of abnormalities in the coordination of and competition between information processing activities in the resting brain of paranoid patients.